Ovarian tissue cryopreservation for fertility preservation: a two-decade single-center experience with 451 children and adolescents - Norah L. A. Emrich; Rebekka Einenkel; Cara Maria Färber; Andreas Schallmoser; Nicole Sänger (Reproductive Biology and Endocrinology)
Abstract Background Ovarian tissue cryopreservation (OTC) is the only fertility preservation option for premenarcheal girls before gonadotoxic treatment, but is still considered to be experimental in pediatric patients. This study investigated storage behaviors across different age groups to refine counseling approaches for pediatric patients. Methods This retrospective study analyzed data from children (0–14 years), adolescents (15–19 years), and adults (≥ 20 years) who underwent OTC between 2000–2021 at the University Hospital Bonn's cryobank. Comparison to adults (age ≥ 20 years) was conducted. Results Of 2,475 patients, 6% were children and 12% adolescents. Sarcoma was most common in children, lymphoma in adolescents. Adults had longer active storage than children (5.5 vs. 4.7 years, p = 0.011), but for active storage ≥ 10 years, children and adolescents stored longer than adults (13.1 and 12.6 vs. 11.8 years, p ≤ 0.01). The proportion of adolescents increased, while that of children decreased in long-term storage. Median ovarian cortex surface before cryopreservation was 3.5 cm2 in children and 4.5 cm2 in adolescents. Leukemia and sarcoma had the highest mortality rates in children (25% and 13.5%). Overall, pregnancy and birth rates following ovarian tissue transplantation (OTT) were 34.5% and 24.1%, respectively. Among adolescents, pregnancy rates were 33.3% after OTT and 27.3% without OTT, while all children without OTT achieved pregnancy (100%). Conclusions Children and adolescents represent a small subset of OTC patients, with indications linked to common pediatric malignancies. For active storage ≥ 10 years, they store longer than adults, likely due to delayed reproduction or awaiting in vitro growth / in vitro maturation in hematological cases. Overall, adults store longer, but adolescent storage has risen over time possibly due to higher child mortality and previously limited OTC use in younger patients. Mean ovarian cortex surface data may guide pediatric tissue harvest recommendations, with unilateral oophorectomy advised. Fertility preservation counseling and cost coverage should be standard for pediatric patients undergoing gonadotoxic treatment. A tailored approach to OTC indications is essential, especially in high-mortality cancers like leukemia or sarcoma. Favorable pregnancy rates observed, even without OTT, suggest possible OTC overutilization, highlighting the need for individualized strategies and careful clinical decision-making to balance risks and preserve reproductive potential.